Perlindungan Hukum terhadap Anak Korban Tindak Pidana Pencabulan di Kabupaten Malaka - Yoaclino De Vedruna Ximenes; Adrianus Djara Dima; Deddy R. Ch. Manafe (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Children are a trust and gift from the Almighty God in whom the honor and dignity of being a complete human being is inherent. Every child has dignity that should be upheld and every child born must receive their rights without the child asking. It's time for the wrong paradigm that thinks children have no rights and must always obey their parents. One of the problems of violence against children is sexual violence which is the focus of this research. The cases of violence that occur are one of the weaknesses in legal protection and protection of the human rights of children who are victims, even though it is the children who must be protected. Children's rights have been expressly stated in the constitution, that the state guarantees every child the right to survival, growth and development and the right to protection from violence and discrimination. The best interests of children need to be respected, as the best interests for the survival of humanity. So that everyone always tries to ensure that children do not become victims of violence, or children fall into committing evil acts or other disgraceful acts. In general, criminal law was born to regulate and organize community life in order to create and maintain public order. Thus, before using crime as a tool/sanction, it is necessary to understand the tool itself. The Criminal Code as the parent or main source of criminal law has detailed the types of crimes, as formulated in article 10 of the Criminal Code. The research results show that the legal process in Malacca Regency is running as the law should, while the research results regarding child protection are not running or being implemented as well as possible due to the lack of legal assistance in the form of safe houses for women and children, psychologists and so on. Lack of direct support from the government itself in handling cases that occur. It is only limited to outreach to residents regarding the impacts and things that should be done to achieve harmony within the families of Malacca Regency itself.